LPG gas leaking detector using arduino for household application - Hasim, Nur Aiman Hanis; Azmi, Ezzatul Farhain; Mohd Zabidi, Muhammad Izzat Zakwan; Mohd. Zabidi, Muhammad Izzat Zakwan; Sanusi, Nortazi (Asian Research Publishing Network (ARPN), 2023)
Nowadays people are busy with work for full fill our daily life hence we forget to care about the small matters in our living area, especially in the kitchen household such as Liquefied Petroleum Gas (LPG) stove. Leaking of LPG can happen without we notice that when the LPG has some or small leakage either from the rubber tubing, faulty regulator fitting, and poor handling of gas appliances that can affect to the house or risk the life of the living persons in the house. Besides that, this gas is colorless and odorless which makes us not notice it. The main objective of this project is to study the operation of Arduino and GSM modules on LPG detectors. Other than that, to develop a programming software system for Arduino. This System design consists of two main modules: detection and transmission module, and receiver module. Detection and the transmission module detect gas changes in concentration using special sensing circuits built for this aim. This module checks for changes in concentration gas has exceeded a predetermined limit and the receiving module functions as a cellular alarm device to allow it mobility in the house. This project is focusing on the product that will be created and the effectiveness of the product on the household application. This project had achieved the objective that has been stated and it is successfully functioning